1989
DOI: 10.1007/bf00131534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing spatial scale on the analysis of landscape pattern

Abstract: The purpose of this study was to observe the effects of changing the grain (the first level of spatial resolution possible with a given data set) and extent (the total area of the study) of landscape data on observed spatial patterns and to identify some general rules for comparing measures obtained at different scales. Simple random maps, maps with contagion (i.e., clusters of the same land cover type), and actual landscape data from USGS land use (LUDA) data maps were used in the analyses. Landscape patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
446
1
27

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 851 publications
(489 citation statements)
references
References 15 publications
15
446
1
27
Order By: Relevance
“…Through our use of accurate DTMs we have achieved a measurement resolution sufficiently fine to distinguish broadly similar sub-sites as topographically and functionally different. This spatial grain was also appropriate for assessing topography at a resolution that individual seals use when making decisions (Forman & Gordon 1986, Kolasa & Rollo 1991, Turner et al 1989, Wiens 1989. Our topographic analyses suggested that the Tarbet site was a relatively higher "cost" site than that of WRB.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Through our use of accurate DTMs we have achieved a measurement resolution sufficiently fine to distinguish broadly similar sub-sites as topographically and functionally different. This spatial grain was also appropriate for assessing topography at a resolution that individual seals use when making decisions (Forman & Gordon 1986, Kolasa & Rollo 1991, Turner et al 1989, Wiens 1989. Our topographic analyses suggested that the Tarbet site was a relatively higher "cost" site than that of WRB.…”
mentioning
confidence: 88%
“…Whilst it may be obvious that topography is likely to impact significantly on an individual animal's behaviour (Stamps 1995) topography is quantified at a spatial grain relevant to the behaviours being studied, that is, at a resolution whereby topographic features will actually impact upon individuals' decision making processes (Forman & Gordon 1986;Turner et al 1989;Wiens 1989). Very few studies have achieved both these aims (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties in collecting data at multiple scales of observation have forced most studies of scale effects to concentrate on the scales of analysis. A common approach is to obtain data at one scale of observation, artificially change the grain or extent of the map data through rescaling, and perform analysis and modeling with the newly generated multi-scale data ͑Gard-ner et Turner et al 1989;Wu 2000;Wu 2003;Saura and Martinez-Millan 2001;. Changing scale by manipulating data can be a surrogate for observing the landscape directly with two or more sensors ͑or sampling schemes͒ of different resolutions.…”
Section: Confusion Between the Scales Of Observation And Analysismentioning
confidence: 99%